Internalization Strategy of Religiosity Values as an Effort to Prevent Bullying at Darul Qur'an Islamic Boarding School Surakarta - Fadhia Ananda; Mahasri Shobahiya (Universitas Muhammadiyah Surakarta, 2025)
This study aims to analyze the strategy of internalizing religiosity values as an effort to prevent bullying in the Darul Qur'an Islamic Boarding School in Surakarta. Bullying, which often appears in verbal and relational forms, is a problem that affects the mental health and social development of students. This study uses a qualitative approach with a case study design to explore an understanding of how religious values are applied in daily life in pesantren and how it contributes to preventing bullying behavior. Data collection was carried out through in-depth interviews with students and pesantren managers as well as the study of documents related to pesantren policies and religious activities. The results of the study show that routine religious activities, such as congregational prayers, dhikr, and learning the Qur'an, play an important role in shaping the character of students who prioritize positive moral and social values. However, although religiosity has a big role in preventing bullying, there are still challenges related to differences in perceptions among students about bullying behavior. In conclusion, the consistent and deep internalization of religiosity values can create a safer and more harmonious environment in Islamic boarding schools, while reducing the risk of bullying.